The Diary of a Teenage Health Freak - McPherson, Ann and Macfarlane, Aidan; Illustrated by Astrop, John (New York Oxford University Press, 1987)
This best-selling guide to teenage health shows that health education can be fun to read about. It features over 50 cartoons by top artist John Astrop.
Include illustrations and index
Keywords: Youth--Health and hygiene -- Teenagers--Health and hygiene -- Health